Team improvised adaptation: team performance in contexts of uncertainty and time scarcity - Abrantes, António da Cunha Meneses Martins (2017)
The main goal of this thesis is to propose, validate, and analyse the team improvised adaptation construct. It comprises one theoretical study and four empirical studies. Team improvised adaptation is the process of team adaptation when design and execution merge. Study 1 deconstructs and recombines team adaptation and team improvisation, proposing the team constructs of purposive improvisation, improvised adaptation and preemptive adaptation. Study 2 validates team improvised- and preemptive adaptation, revealing the moderation role of team learning behaviours on the mediation of improvised adaptation between shared temporal cognitions and team performance. Study 3 suggests that in-action and transitional reflexivity moderate the relationship between shared mental models similarity and improvised adaptive performance, and that transitional reflexivity moderates the relationship between shared mental models similarity and improvised adaptation learning. Study 4 uncovers the mediation effect of team improvised adaptation between future-orientation elevation and team performance. The findings also show that futureorientation diversity has a positive impact on team improvised adaptation learning. However, future-orientation elevation and future-orientation diversity have negative impacts on improvised adaptation learning and team performance, respectively. Finally, study 5 takes an inductive approach revealing two tensions of team improvised adaptation: a deployment tension between routine inertia and improvisation pressures, and a development tension between the need to plan and the need to act immediately. The resolution of these tensions unravels a process that ultimately leads to team learning outcomes. The thesis contributes to the understanding of teamwork, in particular when teams have to adapt to unexpected circumstances under conditions of extreme time scarcity.